Behavioral variations among vascular cognitive impairment subtypes – A comparative study. Issue 4 (4th July 2023) - Bhat, Ashwani; Biswas, Atanu; Das, Gautam; Lahiri, Durjoy; Dubey, Souvik; Mukherjee, Adreesh
Abstract: Dementia of vascular origin is a distinct variety with a heterogeneous neuropsychological profile. Very few studies have compared the behavioral dysfunction in the large vessel and small vessel vascular dementia (VaD) and studied the association between executive dysfunction and behavioral dysfunction documented in these patients, between the white matter load in small vessel disease (SVD) and the behavioral dysfunction. 76 patients having a modified Hachinski Ischemic Scale score of ≥ 4 were recruited and categorized into a small vessel and large vessel VaD. The Neuropsychiatric Inventory (NPI) score ≥ 4 per domain for defining clinically relevant symptoms and the Clinical Dementia Rating Scale (CDR) for evaluating the severity of dementia were used. Behavioral and Psychological Symptoms of Dementia (BPSD) were present in 66.67% of patients with SVD and 53.57% of those having large vessel disease. Apathy, euphoria, and disinhibition were more common in SVD, while appetite alterations were more common in large vessel disease. Behavioral dysfunction was also associated with executive dysfunction in both the VaD subtypes and with white matter loads in SVD. We conclude that different VaD subtypes have different behavioral profiles. This might help in understanding the underlying pathophysiology, diagnosis and thus better management of this disorder.